A repercussão geral no direito brasileiro e os critérios adotados pelo Supremo Tribunal Federal para selecionar as matérias de acordo com a lei n.11.418/2006 - Araújo, Jorge Antônio Cavalcanti (2011)
The improvement of services to under jurisdiction faces a conflict between the need to offer solutions to society ever more rapidly over disputes that it produces and the maintenance of social achievements of great importance, obtained throughout history based on great sacrifice. In this context, the Constitutional Amendment No. 45, December 8, 2004, among other innovations, added to the list of fundamental rights listed in art. 5, of our Constitution, the right to a reasonable duration of the process and means to ensure the speed of its course, and began requiring in the extraordinary is that the passing of the issues discussed in the constitutional case. This institute was regulated by Law No. 11,418 of December 19, 2006, which, however, not exhausted all the matter and left gaps that require some questions about its applicability, a burden on the Supreme Court's role to select which themes are put in this new order, that is, whose interests go beyond the individuality of each party involved in specific cases, which could result in the emergence of conflicts between the thought of Praetorium Exalted and interests of the parties, causing the quickly in providing a court from increasing of filtering procedure eventually might clash with other fundamental rights already enshrined in our legal system. Know what are the criteria adopted by most members of the largest Court of Justice of Brazil to recognize the overall impact because of the relevant issues from the standpoint of economic, political, social or legal, exceeding the subjective interests of the cause of this object reflects the study. Furthermore, the decisions of the STF recognized that the overall impact in the second half of 2010 will be analyzed in order to find out if only the legal aspects were adopted by Praetorium Exalted or other subjective criteria were used to bolster the understanding of Court, demonstrating that the practice of judicial activism is a natural tendency to increasingly delimit the Supreme Court